Tinjauan Yuridis Sanksi Pidana Delik Perbuatan Cabul terhadap Anak dalam Undang-Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak dan Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Muhammad Ikhwan Adabi; Apri Rotin Djusfi; Eza Aulia; Phoenna Ath Thariq; Chandra Darusman; Jefrie Maulana (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
This study focuses on sexual crimes in the form of obscene acts against children. According to R. Soesilo, obscene acts are all acts that violate decency or decency, or can also constitute a heinous act that is included in the environment of sexual lust. The problem lies in the criminal sanctions regulated between the two regulations. Criminal sanctions regulated in the PA Law and the PKS Law have differences in terms of the length of the sentence, the amount of the fine, and others. Then there will also be a test of the PA Law and the TPKS Law against the theory of the purpose of punishment. The research method used is a normative research method, namely research conducted with reference to the principles, legal concepts, legal norms contained in the legislation. The results of this research are that in terms of the comparison of the length of imprisonment or the number of fines, the PA Law is more effective than the TPKS Law. There are also articles regulated in the PA Law that are not regulated in the TPKS Law, such as Articles 76D and 76E. In the article, it is more specific how to commit obscene acts, namely by means of "threats of violence and violence." Both the PA Law and the TPKS Law adhere to a combined theory. In the PA Law and the TPKS Law, the main punishments regulated are imprisonment, fines and payment of restitution to victims. If it is related to the combined theory, then the PA Law and the TPKS Law have fulfilled the purpose of the combined theory. However, in the TPKS Law, in addition to stipulating the main punishment, it also regulates additional crimes, namely revocation of child custody or revocation of guardianship, announcement of the identity of the perpetrator and/or confiscation of profits and/or assets obtained from criminal acts of sexual violence. With the provision of additional penalties in the TPKS Law, it can be seen that the types of criminal sanctions in the TPKS Law provide more complete understanding of the combined theory. So that it can be concluded that the TPKS Law in terms of types of criminal sanctions is more comprehensive in its arrangement.